A total institution within reach? : Music education at Framnäs Folk High School in the 1950s and 60s - Brändström, Sture; Larsson, Anna (Luleå tekniska universitet, Musik och dans, 2011)
The purpose of this article is to increase understanding of what music studies at a folk high school could mean to individual students, and to discuss what Framnäs Folk High School meant to music education opportunities in northern Sweden. The 1950s and 1960s are primarily addressed, in other words, the period from the foundation of Framnäs up until the major changes that took place in the 1970s. How were students recruited, and what did the new study opportunities mean to prospective students? What was the study situation like at the school and what was the social environment like? What role did music play in the study environment and what view towards music found expression at Framnäs Folk High School? Terms used in the analysis include “total institution” (Goffman 1961) and “reach” (Kåks & Westholm 1998). The argument in the article uses analysis of archived material from Framnäs Folk High School, published literature and interviews with former students. In the study, it is shown that Framnäs Folk High School’s music education was within mental reach for many who would hardly have seen the Royal School of Music in Stockholm, at the time Sweden’s northernmost institution for advanced music, as an alternative. The social environment at Framnäs included elements of control and discipline, as well as community and consideration. Something that distinguishes the folk high school environment from total institutions in Goffman’s sense of the term is the camaraderie between teachers and students and the fundamental freedom. The view towards music and culture that characterised the music education at Framnäs may be described as admiring appropriation of the bourgeois or classical music heritage. Validerad; 2011; 20110615 (johsod)